If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-2y)(-7y) = 0 Remove parenthesis around (-2y) -2y(-7y) = 0 Remove parenthesis around (-7y) -2y * -7y = 0 Reorder the terms for easier multiplication: -2 * -7y * y = 0 Multiply -2 * -7 14y * y = 0 Multiply y * y 14y2 = 0 Solving 14y2 = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '14'. y2 = 0 Simplifying y2 = 0 Take the square root of each side: y = {0}
| -7z+15z= | | 5a+6x-x-3a= | | 3x-7=97-10x | | 2-2v=16 | | 14x-7=92 | | 3x+9=60 | | 17x-12=144+3x | | A=2h(a+b) | | 10=6+7 | | 1=2r-7 | | (5x+2)=5 | | -15(12)= | | 4x+3=-3x-4 | | 2(r-3)=0 | | 6x+2y=18 | | 6x+4=3x+28 | | y+(-4)=9 | | 14-7(x+1)=3x-9 | | -am*am*3m= | | x=309-d | | 23y-500=73y-100 | | 3k-17=4 | | 15ab-32ab^2= | | -6p+11=2p-13 | | 2(2f+4)=4(f+2) | | 1-2(3a-5)=3(-2a+1)+8 | | 16t^2-484=0 | | 12x+8=7x+2 | | x+6=6x-66 | | 16y+2x=18 | | -7(-3x-6)=84 | | 16x+2y=18 |